United States (USA) Economic Policy Towards International Recession - Stanfort, Steven William; Victoria, Ong Argo (Law Development Journal, 2025)
Abstract. Being a large superpower, the US is not immune from the crisis. In 2008, the US experienced a crisis in its economy. Many economists argue that the economic crisis in the United States which has not completely ended until now was caused by subprime mortgages. This US securities crisis has spread to all corners of the world, Alan Greenspan, former Governor of the US Central Bank said that this financial crisis is an event that occurs once every 100 years, "Fasten your seatbelt, we're facing the global financial crisis" is a warning issued by Alan Greenspan regarding this global financial crisis. Mortgage in this case is a debt to buy property where the property is then used as collateral (Home Ownership Credit). Mortgage loans are divided into two types; Prime Mortgage & Subprime Mortgage. Simply put, subprime mortgages are mortgages with higher risks. Prime mortgages are usually given to borrowers who meet 2 criteria. First, borrowers who have a good credit history (eg never bankrupt, not late in paying bills). Second, can show the capacity to repay the debt (eg large income, low loan-to-property ratio, etc.). Subprime mortgages are loans to people who do not meet the above criteria. Qualitative methods were used and the theory of adaptive foreign policy models was applied. The results of the study found that the US policy of raising import tariffs that triggered a trade war was influenced by three variables. The external change variable is the emergence of China as a new superpower. The structural change variable is obtained from the change in the US political structure from the Democratic Party to the Republican Party. From the leadership factor, namely Trump's negative perception of China since before he became president. The conclusion is that the policy is a convulsive type adaptive foreign policy that describes significant changes in both the external and internal environments.Keywords: Compulsive; Leadership; Republican; Subprime.